IDENTIFIKASI TANAMAN RAMBUTAN (NEPHELIUM LAPPACEUM L.) LOKAL KABUPATEN BENGKALIS BERDASARKAN KARAKTER MORFOLOGI - Solihin; Aslim Rasyad; Isnaini (UIR Press, 2021)
Even though rambutan is originating from Indonesia, its variability tents to decrease due to farmer selection to plant marketable varieties. The objectives of this study are to determine the diversity of several morphological characteristics and to analyse the relationship among rambutan plants in Bengkalis Regency. Thirty-one plants were chosen by purposive sampling in five districts of the Bengkalis Regency. Every plant was identified its morphological characteristic, including leaves, flowers, fruit, and seed characteristics. In general, most leaves, flower, fruit, and seed characteristics had from low to moderate variability. Tree characteristics, including canopy type growth habits and leaves length had high variability. Cluster analysis indicated that thirty-one plants were divided into three groups, namely group one consisted of two plants, group two consisted of 11 plants, and group three consisted of 18 plants.